Addis Ababa light rail transit system energy flow analysis - Belay, Asegid; Biru, Getachew Getachew (Zede Journal of Ethiopian Engineers and Architects, 2023)
With the continued focus on growing energy prices and environmental concerns, lowering energy consumption and maintaining the environmental sustainability of railway systems is becoming a crucial problem to which greater attention is being paid. In recent years, urban rail systems have grown in popularity as a method for reducing traffic congestion and pollution in metropolitan areas. Despite the fact that the railway system is likely the most energyefficient mode of land-based transportation, there is still potential for improvement. In this regard, significant amounts of energy can be saved by installing energy storage on an electrified transit system allowing energy from braking to be captured. However, the amount of energy saved is dependent on the amount of energy transferred during braking, which relies on the drive cycle and the vehicle parameters. The overall benefit can be determined by analyzing the energy flow through components in an electrified transit system. In this paper, electrified transit system energy flows are analyzed for Addis Ababa light rail transit system. The methodology used assesses energy flows in the traction system, establishing where energy is dissipated. The analysis is performed for a specified drive cycle. Finally, the analysis showed that 37.9 % of the total energy loss over a drive cycle could be saved in Addis Ababa light rail transit system.